Femtosecond writing of refractive index structures in multimode and multicore optical fibres. (December 2018) - Wolf, A.A.; Dostovalov, A.V.; Wabnitz, S.; Babin, S.A.
Abstract: The possibility of writing fibre Bragg gratings (FBGs) in optical fibres with a complex spatial structure using femtosecond IR laser pulses is considered. In particular, selective writing of uniform FBGs in individual cores of a seven-core fibre and writing of serial and parallel FBG arrays in the core of a multimode fibre with a gradient refractive index profile are demonstrated.